RESPONS TAFSIR AL-QUR’AN TERHADAP TANTANGAN ARTIFICIAL INTELLIGENCE (AI) DI ERA BONUS DEMOGRAFI DALAM MEWUJUDKAN PERADABAN - Zukhruful Irbah; Nur Adinda; Fujianti Amellia (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2024)
There have been many articles discussing the negative impact of technological developments on human life, but not many articles have discussed how the Qur’an responds to this problem. This article discusses the interpretation of M. Quraish Shihab in Tafsir Al-Mishbah and its contextualization as a solution to the challenges of AI in the era of the demographic bonus to create a quality civilization. This article focuses on the interpretation of M. Quraish Shihab in QS. al-Nazi’at (79): 40, QS. al-Ahzab (33): 21, QS. Yunus (10): 100, QS. al-’Ashr (103): 1-3 and QS. al-Taubah (9): 105. The researcher used a content analysis study of this interpretation with sociological analysis. This research confirms that in facing the challenges of AI in this demographic bonus era, the spirit of the Koran encourages humanity to increase self-control to the maximum. The Qur’an provides a comprehensive guide for human life which includes character education, morality, time management, and self-control, as well as encouragement to strive to achieve a wise life amidst the very rapid development of technology.